2005
DOI: 10.1073/pnas.0506897102
|View full text |Cite
|
Sign up to set email alerts
|

Training, maturation, and genetic influences on the development of executive attention

Abstract: A neural network underlying attentional control involves the anterior cingulate in addition to lateral prefrontal areas. An important development of this network occurs between 3 and 7 years of age. We have examined the efficiency of attentional networks across age and after 5 days of attention training (experimental group) compared with different types of no training (control groups) in 4-year-old and 6-year-old children. Strong improvement in executive attention and intelligence was found from ages 4 to 6 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
702
0
14

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 953 publications
(770 citation statements)
references
References 29 publications
(41 reference statements)
42
702
0
14
Order By: Relevance
“…Although a number of studies have reported an influence of the 10-repeat allele of the 3 0 -UTR VNTR on cognitive or physiological measures in both healthy and clinical populations, 23,24,[34][35][36][37] the current report is the first to demonstrate an effect of the 3-repeat intron 8 allele on cognitive measures in healthy children. Linking allelic variation in a polymorphism to cognitive measures is an important way to establish the functional significance of that polymorphism.…”
Section: Discussionmentioning
confidence: 78%
“…Although a number of studies have reported an influence of the 10-repeat allele of the 3 0 -UTR VNTR on cognitive or physiological measures in both healthy and clinical populations, 23,24,[34][35][36][37] the current report is the first to demonstrate an effect of the 3-repeat intron 8 allele on cognitive measures in healthy children. Linking allelic variation in a polymorphism to cognitive measures is an important way to establish the functional significance of that polymorphism.…”
Section: Discussionmentioning
confidence: 78%
“…Comparable studies with older children have generally found that training effects, where detectable, tend to be maintained at intervals ranging from two months to a year (Dunning et al, 2013;Klingberg et al, 2005;Rueda, Rothbart, McCandliss, Saccomanno, & Posner, 2005). However, it is unknown whether training effects are as persistent in infants.…”
Section: Introductionmentioning
confidence: 99%
“…inhibitory or effortful control) may mediate effects of preterm birth on cognitive outcomes [7,8] and later achievement [9,10]. Inhibitory control predicts the development of the executive attention network [11] and is related to children's executive functions (EFs), high-level cognitive abilities that allow humans to show adaptive, goal-directed behavior in complex situations [12]. In an ever-changing and unpredictable environment, EFs, and self-control in particular, are not only vital to master real-life situations but also predict long-term academic achievement [13][14][15].…”
mentioning
confidence: 99%